'De la Rey' and the Revival of 'Boer Heritage': Nostalgia in the Post-apartheid Afrikaner Culture Industry - van der Waal, Kees (C.S.); Robins, Steven (Journal of southern African studies, 2011)
An Afrikaans popular song about a general of the Anglo-Boer War, 'De la Rey' was received with great enthusiasm among white Afrikaans-speakers in 2007, but also generated much controversy about the possible implications of re-ethnicisation among Afrikaners. What did this manifestation of popular culture say about the resilience of Afrikaner identity and the impact of the New South Africa? This article examines the ways in which this song entered into the post-apartheid public sphere, and investigates how De la Rey revivalism can be related to Afrikaners' experience of post-apartheid transformation. The 'De la Rey song' was created for a market that was ripe for a nostalgic celebration of a revamped but less party-political Afrikaans ethnic identity. The song soon became a rallying point for Afrikaners who perceived themselves to be under threat from the ANC government. The heroic figure of De la Rey was invoked as a saviour who would be able to lead the threatened Afrikaners symbolically to a safe place. The song tapped into the profoundly unsettled identity politics of many white Afrikaans-speakers whose continued commitment to a racially exclusivist identity was no longer politically acceptable. The song succeeded because it was a muted affirmation of white Afrikaner identity and helped to reassert the imagined boundaries of white Afrikanerdom while speaking the legitimate language of history and cultural heritage.